MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA PROYEK UJI COBA SKALA PENUH JEMBATAN CABLE STAYED UNTUK LALU LINTAS RINGAN - Setyo Hardono; Nazib Faizal; Rulli Ranastra Irawan (Direktorat Bina Teknik Jalan dan Jembatan, 2009)
An accident occurred on site caused by human error and technical error. To reduce and insure this, we have to perform Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3). SMK3 similar to Health, Safety, and Environment Procedure (HSE Procedure).In this paper, we describe about SMK3 system in Cable Stayed Project in Sukabumi, Jawa Barat, its contain organization structure, risk assesment, personal protection equipment, emergency response, regulation of health and environment, medical regulation, and safety regulation. Keywords : safety, health, accident, work, risk assessment, emergency response